Web-based spatial data infrastructure: a solution for the sustainable management of thematic information supported by aerial orthophotography (2013)
Under the framework of the Spanish National Plan for Aerial Orthophotography in Castilla-La Mancha, a web-based spatial data infrastructure has been developed that allows both the sustainable management of spatial and thematic information and efficient quality control of orthophoto production. The dissemination of thematic cartographic information by means of false-color infrared images and their physical parameters (reflectance and radiance) could allow its use in applications such as the extraction of biophysical parameters, forest coverage evolution and vegetative analysis of species. For wide accessibility, a geoportal that offers all the information related to the project and based on spatial data infrastructure technology has been created (http://ide.jccm.es/pnoa) that incorporates web map services.